A Virtual Point‐of‐care Ultrasound Course During the COVID‐19 Pandemic. Issue 1 (9th November 2020) - Lin, Sophia D.
Abstract: Due to the COVID‐19 pandemic, in‐person educational activities for emergency medicine (EM) residents were suspended. As a result, we developed a virtual point‐of‐care ultrasound (POCUS) course for incoming EM interns consisting of online didactics and faculty‐proctored hands‐on scan sessions utilizing a video conferencing platform and a handheld smartphone‐compatible ultrasound transducer. Learners found the course to be effective in improving their POCUS knowledge and scanning skills. Feedback obtained from this course will allow us to improve future virtual courses.